Project Management and Cost Optimization in QR Code-Based Parking Reservation System Development: A PERT, Monte Carlo and PMBOK Approach - Yostian Ari Sujarwo; Samidi (ULTIMA InfoSys, 2025)
This paper explores the project management practices and cost optimization outcomes associated with the development of an in-house parking reservation system utilizing QR code technology. The main objective of this project was to implement structured project management methodologies to ensure successful system delivery while minimizing project losses. The approach involved detailed planning, execution, monitoring, and closure activities aligned with the PMBOK framework. To enhance cost efficiency, PERT Cost Analysis was applied to refine the cost estimates, while Monte Carlo Simulation was used to analyze cost uncertainty and variability. These methods enabled the team to reduce the projected human resource cost from IDR 748 million to IDR 403 million, demonstrating significant cost savings. Furthermore, robust risk management strategies supported effective decision-making and stakeholder alignment throughout the project. This study provides practical insights into integrating quantitative analysis into project cost control and offers guidance for managing similar technology implementation projects in the future.